Identity transformation of Josephine Alibrandi and John Barton in the Novel Looking for Alibrandi (by Melina Marchetta) - Ferdi, Ferdi (UI Scholars Hub, 2013)
This paper examines the progress of identity transformation of Josephine Alibrandi and John Barton in the novel Looking for Alibrandi. Josephine and John come from different family backgrounds. Josephine comes from an Italian immigrant family who lives in suburban area, while, John Barton comes from a politician family in Australia. Although they come from different family backgrounds, they still have the same problems in their identities. Their desire to be seen as themselves in the society makes them intend to find their identity. The reason I intend to do a research in this novel because I think this novel is interesting for teenagers and it can inspire them to find their identity in the society. Identity transformation is something that should and will occur in anyone’s life. Josephine Alibrandi and John Barton represent the general group of teenagers in the world in terms of gender and social class. Each individual, however, have their own solution and way to find their identity. This paper concludes that identity transformation happens in both Josephine Alibrandi and John Barton in different ways. Each of them also has different strategies to overcome the problem and they also get different results.